Perbandingan Kepemimpinan dalam Sekolah dan Pondok Pesantren - Moh. Soleh; Supardi Supardi (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article discusses the comparison of leadership in the context of schools and Islamic boarding schools. Leadership in educational institutions is very important for achieving academic goals and developing student character. However, leadership in schools and Islamic boarding schools differs in culture, values, and institutional goals. This study uses a qualitative approach with data collection techniques through in-depth interviews with school and Islamic boarding school leaders. Data analysis was performed using the thematic analysis method. The results of the study show that leadership in schools is more focused on administrative management, while leadership in Islamic boarding schools is more focused on building religious character and values. In addition, leadership in Islamic boarding schools is more paternalistic in nature, while leadership in schools is more democratic. In the context of educational development in Indonesia, this research can provide insight and understanding of the differences in leadership in two different types of educational institutions. It is hoped that the results of this research can provide guidance for leaders of educational institutions in improving the quality of leadership and educational development in Indonesia.